2013
DOI: 10.1890/12-1511.1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive thermoregulation during summer in two populations of an arid‐zone passerine

Abstract: Abstract. Heterothermy plays an important role in lowering the costs of thermoregulation in endotherms by reducing water and energy requirements. We tested predictions that birds in arid habitats should express fine-scale variation in their thermoregulatory patterns as a function of prevailing climatic conditions. We assessed effects of air temperature (T air ) and water vapor pressure deficit (D) on body temperature (T b ) in free-living White-browed Sparrow-Weavers (Plocepasser mahali ) during summer in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
112
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(126 citation statements)
references
References 57 publications
11
112
0
Order By: Relevance
“…In contrast to these free-ranging populations, our laboratory data for P. mahali ( present study) and those of Trost (1972) on E. alpestris reveal lower T b in desert than in mesic populations at high T a . Moreover, free-ranging sparrow-weavers commenced panting at T a >28°C (Smit et al, 2013), whereas our limited behavioural observations indicated that birds in the laboratory started panting at a substantially higher T a across all sites (mean T a at onset of panting=36.8±2.7°C; lowest T a =32.0°C). These differences likely reflect the very low chamber humidities in the present study and the effects of solar radiation on the operative temperatures experienced by free-ranging sparrow-weavers.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…In contrast to these free-ranging populations, our laboratory data for P. mahali ( present study) and those of Trost (1972) on E. alpestris reveal lower T b in desert than in mesic populations at high T a . Moreover, free-ranging sparrow-weavers commenced panting at T a >28°C (Smit et al, 2013), whereas our limited behavioural observations indicated that birds in the laboratory started panting at a substantially higher T a across all sites (mean T a at onset of panting=36.8±2.7°C; lowest T a =32.0°C). These differences likely reflect the very low chamber humidities in the present study and the effects of solar radiation on the operative temperatures experienced by free-ranging sparrow-weavers.…”
Section: Discussionmentioning
confidence: 56%
“…It is also possible that maintaining a lower T b has an adaptive value by providing a greater capacity for heat storage before lethal T b limits are reached (McNab and Morrison, 1963;Tieleman et al, 2002a). Smit et al (2013) found that in two free-ranging populations of P. mahali in the Kalahari Desert, the T b set-point was significantly higher in a desert (41.5±0.2°C) versus semi-desert population (40.2±0.2°C), but that the desert population did not have a greater capacity for hyperthermia (i.e. T b >modal T b values).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only a handful of studies have documented the nocturnal energetic strategy of free-ranging passerines, and even fewer have measured core T b . White-throated sparrows (Zonotrichia albicollis) have a rest-phase hypothermia, with a 3.4°C reduction in T skin between active and rest phase (Dolby et al, 2004) and the diel variation in T b of the arid-dwelling white-browed sparrow-weaver (Plocepasser mahali) is attributed to seasonal environmental conditions (Smit et al, 2013). The only comparable measurement of continuous, nocturnal T b of an Australian passerine in the cold is for captive-raised juvenile dusky woodswallows (Artamus cyaneurus; Maddocks and Geiser, 2007), measured in outdoor aviaries.…”
Section: Discussionmentioning
confidence: 99%